Techniques For Memorizing Hadith Using The Muhafazoh Method Strategy 5.5 (Phenomenological Study Of The National Level Stqh Hadith Musabaqoh) - Juli Julaiha P; Sri Ulfa Rahayu (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The existence of inkarsunnah makes the preservation of the Hadith of the Prophet SAW very necessary. Among them is the Muhafazoh Method strategy 5.5. This method was applied, among others, by the participants of the Hifzilhadis branch of the North Sumatra Province delegation in the National Tilawatil Quran and Hadith Selection (STQH) event. The Muhafazoh method strategy 5.5, namely the first 5 are intention, al-qiraat, fahmul hadith, tikrar, tahdif and targhib. Furthermore, the second 5 are studying to a hadith expert teacher, notes and pens of various colors as markers, sound recordings, locations, and memorization of Hadith. This study uses a qualitative method with a phenomenological approach to analyze the experiences of participants in mastering hadith memorization, including challenges, adaptation strategies, and their impact on memorization success. The results of the study show that the Muhafazoh method strategy 5.5 has been practiced well by participants in memorizing hadith, especially in terms of accuracy and fluency, one of which is this technique using audio media to correct the reading. Thus, the Muhafazoh method strategy 5.5 can be used as an applicable learning model for memorizing hadith, especially in preparation for national level competitions and general learning